Prevalence of Non-Nutritive Sucking Habits and Potential Influencing Factors among Children in Urban Communities in Nigeria - Orimadegun, Adebola Emmanuel; Obokon, Gabriel Omen (Frontiers in Pediatrics, 2015)
Background: The use of non-nutritive sucking materials like pacifiers and fingers poses health challenges to children in resource-limited settings, where hygiene practices and provision of clean water are poor. This study was designed to determine the prevalence of non-nutritive sucking habits and its association with acute diarrhoea in children aged 6 to 23 months in urban communities of Nigeria. Methods: In this cross-sectional study, 12 communities from four out of 12 geopolitical wards in Ibadan North Local Government Area and 427 mothers of children aged 6-24 months were randomly selected. A pre-tested, interviewer-administered questionnaire was used to obtain information on socio-demographic characteristics, recent history of diarrhoea (three months prior to visit) and use of non-nutritive sucking materials. Descriptive statistics, Chi square and logistic regression were used for data analysis at p=0.05. Results: Mean age of the children was 13.9±5.3 months and 50.6% were males. Prevalence of non-nutritive sucking was 45.2%. Prevalence of non-nutritive sucking was not significantly different between males (45.8%) and females (44.5%). The odds of engaging in non-nutritive sucking increases by 6.0% with increasing age (OR = 1.06; 1.02; 1.10). More children who were not exclusively breastfed (53.5%) than exclusively breastfed (26.2%) were likely to engage in non-nutritive sucking (OR = 3.25; 95% CI = 2.07, 5.12). Acute diarrhoea was more frequently reported in non-nutritive sucking group than the other (OR = 1.51; 95% CI = 1.03, 2.22). Conclusion: Non-nutritive sucking was linked with failure to practice exclusive breastfeeding, worse with increasing age and predisposes to acute diarrhoea. Further studies are necessary to verify the nature of these associations.